An observational study to find out incidence and pattern of adverse drug reactions among multidrug resistant tuberculosis patients treated under revised national TB control program of India - Lakhani, Preet; Barua, Shireen; Singh, Divya; Jain, Suchi; Kant, Surya; Verma, Ajay; Sachan, Amod K.; Nath, Rajendra; Dixit, Rakesh K. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Between 2006 and 2015, the prevalence of MDR-TB has been found to be as high as 39.9% in some states. Approximately 35.8% of all previously treated patients developed MDR-TB. The objective of the present study was to identify demographic and health characteristics of patients as well as incidence and pattern of the adverse drug reactions caused by antitubercular drugs in MDR-TB patients in a tertiary care hospital of northern India. Methods: This 12 months study of observational study was conducted at a DOTS centre. MDR-TB diagnosed patients treated with DOTS Plus regimen were enrolled after getting informed consent. Patient information was recorded. Patient follow-up was conducted to identify the incidence and pattern of ADRs. Results: A total of 115 patients were enrolled. Maximum number of cases were in the 31-40 age group (25.21%) followed by the 41-50 age group (20.86%). 76 (66.08%) were males and 39 (33.91%) were females. 52 patients (45.21%) had concomitant diseases, out of which 15 (13.04%) were HIV positive and 21 (18.26%) were diabetic. 70 patients (60.86%) developed ADRs. The adverse drug reaction that were seen are -38 (38.76%) cases of gastrointestinal adverse drug reactions, 8 (8.16%) jaundice/hepatitis, 7 (7.14%) impaired hearing/vertigo, 21 (21.24%) central nervous system adverse drug reaction, 6 (6.12%) peripheral neuropathy, 6 (6.12%) rash and itching, 5 (5.10%) arthralgia, 3 (3.06%) renal impairment, 2 (2.04%) hypothyroidism and 2 (2.04%) blurred vision. Conclusions: Determining which population groups are affected most by ADRs can help physicians to better monitor and make an early diagnosis to reduce ADR-related morbidity and mortality.